The Case for Case Studies Methods and Applications in International Development - Widner, Jennifer; Woolcock, Michael; Ortega Nieto, Daniel (Social Sciences, 2022)
This volume demonstrates how to conduct case study research that is both methodologically rigorous and useful to development policy. It will interest scholars and students across the social sciences using case studies, and provide constructive guidance to practitioners in development and public administration.